2017
DOI: 10.1007/s11356-017-8977-6
|View full text |Cite
|
Sign up to set email alerts
|

Fishing for contaminants: identification of three mechanism specific transcriptome signatures using Danio rerio embryos

Abstract: In ecotoxicology, transcriptomics is an effective way to detect gene expression changes in response to environmental pollutants. Such changes can be used to identify contaminants or contaminant classes and can be applied as early warning signals for pollution. To do so, it is important to distinguish contaminant-specific transcriptomic changes from genetic alterations due to general stress. Here we present a first step in the identification of contaminant class-specific transcriptome signatures. Embryos of zeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 70 publications
1
4
0
Order By: Relevance
“…Overall, the enriched pathways were related to various functions including stress response (adenosine monophosphateactivated protein kinase signaling pathway, FoxO signaling pathway), synthesis and metabolism of biomolecules (glutathione, carbohydrates, steroids), promotion of cell growth, proliferation, and metabolism (PI3K-Akt signaling pathway), DNA repair, mineral absorption, immune response (cytokine-cytokine receptor interaction and antigen processing and presentation), muscle contraction (regulation of actin cytoskeleton), fatty acid and energy metabolism (fatty acid elongation, carbon metabolism), and cell death (apoptosis, ferroptosis, necroptosis). These pathways have similarly been identified in previous transcriptomic studies concerning methylmercury exposure in fish species including rainbow trout (Liu et al, 2013), zebrafish (DeBofsky et al, 2018;Hausen et al, 2018;Zhu et al, 2019), Atlantic cod (Yadetie et al, 2013), and European cusk (Olsvik et al, 2021). Furthermore, an overall examination of the Comparative Toxicogenomic Database (CTD; North Carolina State University, 2022) showed that many of these same pathways were dysregulated in response to exposure to methylmercury compounds (i.e., the top three were metabolism, immune system, and signal transduction).The significantly enriched pathways with the lowest BMD values (i.e., those with pathway BMD values below 10 ppb) included those involved in mineral absorption, metabolism, and biosynthesis (e.g., glutathione metabolism and steroid biosynthesis), and ferroptosis.…”
Section: Pathway-level Transcriptomic Bmd Enrichment Analysissupporting
confidence: 57%
“…Overall, the enriched pathways were related to various functions including stress response (adenosine monophosphateactivated protein kinase signaling pathway, FoxO signaling pathway), synthesis and metabolism of biomolecules (glutathione, carbohydrates, steroids), promotion of cell growth, proliferation, and metabolism (PI3K-Akt signaling pathway), DNA repair, mineral absorption, immune response (cytokine-cytokine receptor interaction and antigen processing and presentation), muscle contraction (regulation of actin cytoskeleton), fatty acid and energy metabolism (fatty acid elongation, carbon metabolism), and cell death (apoptosis, ferroptosis, necroptosis). These pathways have similarly been identified in previous transcriptomic studies concerning methylmercury exposure in fish species including rainbow trout (Liu et al, 2013), zebrafish (DeBofsky et al, 2018;Hausen et al, 2018;Zhu et al, 2019), Atlantic cod (Yadetie et al, 2013), and European cusk (Olsvik et al, 2021). Furthermore, an overall examination of the Comparative Toxicogenomic Database (CTD; North Carolina State University, 2022) showed that many of these same pathways were dysregulated in response to exposure to methylmercury compounds (i.e., the top three were metabolism, immune system, and signal transduction).The significantly enriched pathways with the lowest BMD values (i.e., those with pathway BMD values below 10 ppb) included those involved in mineral absorption, metabolism, and biosynthesis (e.g., glutathione metabolism and steroid biosynthesis), and ferroptosis.…”
Section: Pathway-level Transcriptomic Bmd Enrichment Analysissupporting
confidence: 57%
“…The default EASE threshold of 0.1.0 was used. Global co-expression networks were then constructed using the Cytoscape app GeneMANIA ( Campanaro et al, 2007 ; Montojo et al, 2010 ; Vied et al, 2014 ; Hausen et al, 2017 ). The desired organism used was human, with the options to display up to 50 related genes, 20 related attributes, and automatic weighting.…”
Section: Methodsmentioning
confidence: 99%
“…Open digital repositories can be used to archive current-state full scan HRMS analysis for retrospective and joint exploitation [ 53 , 54 ]. At the same time, a bunch of bio-informatics tools including innovative clustering algorithms from metabolomics and genomics including independent component analysis (ICA) and cytoscape/ClueGO pathway analysis [ 55 , 56 ], hierarchical clustering, K -means, self-organizing maps and fuzzy clustering [ 57 , 58 ] are available and help unravel big and complex analytical datasets. It may be assumed that complex environmental mixtures in water bodies are not just randomly composed but the result of confluence of source-related patterns modified by environmental fate.…”
Section: Advanced Chemical Monitoring and Risk Assessmentmentioning
confidence: 99%